Lesions of lateral or central amygdala abolish aversive Pavlovian-to-instrumental transfer in rats - Campese, Vincent D.; Kim, Jeanny; Lázaro-Muñoz, Gabriel; Pena, Lashawn; LeDoux, Joseph E.; Cain, Christopher K. (Frontiers in Behavioral Neuroscience, 2014)
Aversive Pavlovian conditioned stimuli (CSs) elicit defensive reactions (e.g., freezing) and motivate instrumental actions like active avoidance (AA). Pavlovian reactions require connections between the lateral (LA) and central (CeA) nuclei of the amygdala, whereas AA depends on LA and basal amygdala (BA). Thus, the neural circuits mediating conditioned reactions and motivation appear to diverge in the amygdala. However, AA is not ideal for studying conditioned motivation, because Pavlovian and instrumental learning are intermixed. Pavlovian-to-instrumental transfer (PIT) allows for the study of conditioned motivation in isolation. PIT refers to the ability of a Pavlovian CS to modulate a separately-trained instrumental action. The role of the amygdala in aversive PIT is unknown. We designed an aversive PIT procedure in rats and tested the effects of LA, BA, and CeA lesions. Rats received Pavlovian tone-shock pairings followed by Sidman shock-avoidance training. PIT was assessed by comparing shuttling rates in the presence and absence of the tone. Tone presentations facilitated instrumental responding. Aversive PIT was abolished by lesions of LA or CeA, but was unaffected by lesions of BA. These results suggest that LA and CeA are essential for aversive conditioned motivation. More specifically, the results are consistent with a model of amygdala processing in which the CS is encoded in the LA and then, via connections to CeA, the motivation to perform the aversive task is enhanced. These findings have implications for understanding the contribution of amygdala circuits to aversive instrumental motivation, but also for the relation of aversive and appetitive behavioral control.